2013
DOI: 10.1371/journal.pone.0054906
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Dependent Induction of DNA Damage by 1800 MHz Radiofrequency Electromagnetic Fields Does Not Result in Significant Cellular Dysfunctions

Abstract: BackgroundAlthough IARC clarifies radiofrequency electromagnetic fields (RF-EMF) as possible human carcinogen, the debate on its health impact continues due to the inconsistent results. Genotoxic effect has been considered as a golden standard to determine if an environmental factor is a carcinogen, but the currently available data for RF-EMF remain controversial. As an environmental stimulus, the effect of RF-EMF on cellular DNA may be subtle. Therefore, more sensitive method and systematic research strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 37 publications
(54 reference statements)
4
47
0
1
Order By: Relevance
“…Similarly, the Report correctly lists two studies by Zeni, Sannino and their colleagues as being negative for apparent genotoxicity; however, this same research group published 6 additional studies, with three showing positive effects, depending on the cell type being studied. The Xu et al (59) study found genotoxicity in two cell types but not in four other cell types. These studies clearly show that different types of cells respond differently to low level microwave exposures, but for some reason, the Panel of Experts seems unable to draw this very important conclusion.…”
Section: Genotoxicity Of Non-thermal Microwave Exposures: Examples Ofmentioning
confidence: 93%
“…Similarly, the Report correctly lists two studies by Zeni, Sannino and their colleagues as being negative for apparent genotoxicity; however, this same research group published 6 additional studies, with three showing positive effects, depending on the cell type being studied. The Xu et al (59) study found genotoxicity in two cell types but not in four other cell types. These studies clearly show that different types of cells respond differently to low level microwave exposures, but for some reason, the Panel of Experts seems unable to draw this very important conclusion.…”
Section: Genotoxicity Of Non-thermal Microwave Exposures: Examples Ofmentioning
confidence: 93%
“…The timeframe and lasting effects of low-frequency electromagnetic fields on DNA depend on several factors, such as the cell type, the efficacy of DNA repair (consistent with H2AX dephosphorylation), the mode of exposure, the type of magnetic waves (static magnetic field, radiofrequency pulses, and gradient magnetic fields), the intensity and duration of exposure, and the use of contrast agent. [15][16][17][18][19][20][21] During CMR, all these factors can contribute at different degrees to DNA damage. Iron-mediated reactive oxygen In the study of Fiechter et al, 11 the potentially higher absorbed energy and the concomitant use of gadolinium could participate and potentiate the early onset of DNA strand breaks.…”
Section: Downloaded From Cmr Effects On Blood Cellsmentioning
confidence: 99%
“…Indeed, apoptosis only seems to occur when cellular γ-H2AX levels reach specific threshold values. 16,17,19 Other intracellular abnormalities have been shown to occur during static magnetic fields with changes in erythrocyte membrane permeability, membrane elasticity, and erythrocyte sedimentation rate. 15,21 Neutrophils and monocytes displayed transient expression of activation markers.…”
Section: Cmr and Blood Cell Counts/activationmentioning
confidence: 99%
“…The altered gene expression has to negatively inflict cellular structural and its functional activity with increased tendency to tumor formation [8]. The EMR is recently classified as "possibly carcinogenic to humans" (Group 2B) as indicated by International Agency for Research on Cancer (IARC) [9]. The capacity for malignant growth is acquired by the stepwise accumulation of defects in specific genes regulating cell growth and tissue homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity for malignant growth is acquired by the stepwise accumulation of defects in specific genes regulating cell growth and tissue homeostasis. Many studies suggested that exposure to EMR was associated with a small but significant increase in the risk of cancer [9,10], which could be induced from gene mutations that resulted from DNA damage [11]. The carcinogenic process has three stages: initiation, promotion and progression.…”
Section: Introductionmentioning
confidence: 99%